Najnowszy stereotyp Ukraińca w środowisku studentów poznańskich i lubelskich - Fyłypec, Olga (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article analyses the contemporary image of a Ukrainian in the linguistic picture of the world as perceived by students from Poznan and Lublin. Based on the results of the questionnaire with the geographical factor, the article distinguishes the “naive” cognitive definitions, methods of categorisation, traits of a typical Ukrainian and their aspect, which all differ depending on the geographical location of the two cities. The article analyses which subjects, according to students from different regions of Poland, are characteristic of a Ukrainian and how the geographical factor influences their dominance in the light of different aspects.